DATABASE VULNERABILITY TESTING MEMANFAATKAN SQLMAP PADA UBUNTU 22.04 ( STUDI KASUS : ANTARATECH.NET) - Praptomo, Sidik; Suryanto, Suryanto; Kurniawan, Jefdy (Jurnal Informatika Medis, 2023)
Vulnerability trial of database using SQLMap on Ubuntu 22.04 is an important process to identify security vulnerabilities in database systems running on the Ubuntu 22.04 platform. This study discusses the importance of vulnerability Uji coba in the information security space, with a focus on SQL-based database systems and the Ubuntu 22.04 platform. We describe a vulnerability Uji coba methodology that involves the use of SQLMap, a penetration tool specifically designed to identify SQL injection vulnerabilities. This research covers the basic concepts of SQL injection, the steps of implementing SQLMap on the Ubuntu 22.04 platform, and how to interpret the test results. We also discuss the benefits of using SQLMap, including an in-depth understanding of database vulnerabilities that can help organizations improve the security of their systems. The result of this research is a practical guide to performing database vulnerability testing with SQLMap on the Ubuntu 22.04 platform, thus helping security professionals and system administrators to identify and address potential vulnerabilities that could compromise data integrity and confidentiality. This research makes an important contribution in the effort to maintain the security of database systems in the challenging digital era.